The significance of core theories in the Islamic legal structure: an analysis with reference to the concept of shirkah (partnership) - Sadique, Muhammad Abdurrahman (2009)
Paying due attention to the relevant theoretical foundation is important in developing new rulings for application in fields such as modern banking and finance. Research on the primary layout of shari’ah rulings indicates that in many instances, individual theoretical foundations have served as the basis for all the rulings on a specific legal area. A school’s approach to, and its rulings on, detailed issues related to a subject are shaped by the individual theoretical foundation developed by the school pertaining to the area of law concerned. In capital based partnerships, rulings of each school have been directly influenced by the distinct postulation adopted by the school with regard to the essence of shirkah. The perception of each school regarding the core structure of shirkah has dictated the approach of the school to the admissibility of various types of capital, liability of partners, and a multitude of related rulings. In deriving practical solutions to issues of current relevance, it should be ensured that the rulings reflect a uniform underlying theory, without contradiction at any level. This calls for a careful attempt to discover or remodel theoretical foundations of various topics, which could accommodate all related regulations. In safeguarding the theoretical superiority of the shari’ah, this aspect is of central importance.